2003
DOI: 10.1085/jgp.200308916
|View full text |Cite
|
Sign up to set email alerts
|

S4 Movement in a Mammalian HCN Channel

Abstract: Hyperpolarization-activated, cyclic nucleotide–gated ion channels (HCN) mediate an inward cation current that contributes to spontaneous rhythmic firing activity in the heart and the brain. HCN channels share sequence homology with depolarization-activated Kv channels, including six transmembrane domains and a positively charged S4 segment. S4 has been shown to function as the voltage sensor and to undergo a voltage-dependent movement in the Shaker K+ channel (a Kv channel) and in the spHCN channel (an HCN cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
87
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(104 citation statements)
references
References 28 publications
14
87
3
Order By: Relevance
“…A, Sequence alignment of spHCN and HCN1 S4 domains. Marked residues exhibit state-dependent modification by intracellular (*), extracellular (#), or both intracellular and extracellular reagents (&), or state-independent modification by either intracellular or extracellular reagents (o) (Männikkö et al, 2002;Bell et al, 2004;Vemana et al, 2004). B, C, Representative current (top) and fluorescence (bottom) records from Alexa-488 C5-maleimide-exposed wt spHCN channels (B) and 326C channels (C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A, Sequence alignment of spHCN and HCN1 S4 domains. Marked residues exhibit state-dependent modification by intracellular (*), extracellular (#), or both intracellular and extracellular reagents (&), or state-independent modification by either intracellular or extracellular reagents (o) (Männikkö et al, 2002;Bell et al, 2004;Vemana et al, 2004). B, C, Representative current (top) and fluorescence (bottom) records from Alexa-488 C5-maleimide-exposed wt spHCN channels (B) and 326C channels (C).…”
Section: Resultsmentioning
confidence: 99%
“…2 A) that showed a stateindependent accessibility for N-terminal S4 residues (residues 326 -332 in spHCN channels) (Männikkö et al, 2002;Bell et al, 2004;Vemana et al, 2004). In contrast, residues in the middle and C-terminal end of S4 (residues 333-349 in spHCN channels) are accessible in a state-dependent manner (Männikkö et al, 2002;Bell et al, 2004;Vemana et al, 2004), suggesting that these residues are the voltage-sensing charges that undergo the transmembrane movement that triggers channel opening. The mode shift itself exhibits little, if any, voltage dependence (Elinder et al, 2006), suggesting no large inward movement of the gating charges during the mode shift.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that these channels are differentially sensitive to the direction of the voltage change and that the activation curves in mode I and mode II are separated by up to 50 mV is defined as "voltage hysteresis." This interesting gating behavior of spHCN is probably the result of a slow conformational change attributable to lateral movement of S4 that stabilizes the inward position of S4 upon hyperpolarization (52,53,133,245,246,405). HCN1 channels behave similarly as spHCN channels with respect to hysteresis behavior and mode shift (246).…”
Section: A Transmembrane Segments and Voltage Sensormentioning
confidence: 99%
“…Studies of the S4 segments of HCN channels has confirmed that they move outward upon depolarization like other voltage-gated channels (27)(28)(29), even though HCN channels are activated by hyperpolarization. These results indicate that an alteration in the coupling of outward movement of the S4 voltage sensors to eventual opening of the pore underlies hyperpolarization-activated pore opening in HCN channels.…”
Section: Bending Of S6 Segments Determines Both Voltage Dependence Andmentioning
confidence: 99%